2021
DOI: 10.14366/usg.20007
|View full text |Cite
|
Sign up to set email alerts
|

What shear wave elastography parameter best differentiates breast cancer and predicts its histologic aggressiveness?

Abstract: This study aimed to identify useful shear wave elastography (SWE) parameters for differentiating breast cancer and predicting associated immunohistochemical factors and subtypes. Methods: From November 2018 to February 2019, a total of 211 breast lesions from 190 patients who underwent conventional breast ultrasonography and SWE were included. The Breast Imaging, Reporting and Data System categories and qualitative and quantitative SWE parameters for each lesion were obtained. Pathologic results including immu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 24 publications
4
11
0
Order By: Relevance
“…For quantitative analysis, malignant neoplasms had higher values. In 2D-SWE, eEmax (sensitivity: 86.4; specificity: 96.3) and eEratio (sensitivity: 81.8; specificity: 95.1) showed the best performance, consistent with previous studies ( 5 , 10 , 11 ). In color images, the neoplasm showed a hard ring sign significantly indicating malignancy.…”
Section: Discussionsupporting
confidence: 89%
“…For quantitative analysis, malignant neoplasms had higher values. In 2D-SWE, eEmax (sensitivity: 86.4; specificity: 96.3) and eEratio (sensitivity: 81.8; specificity: 95.1) showed the best performance, consistent with previous studies ( 5 , 10 , 11 ). In color images, the neoplasm showed a hard ring sign significantly indicating malignancy.…”
Section: Discussionsupporting
confidence: 89%
“…In the same study, it was shown that there were significant correlations between SWE stiffness rates and lymphovascular invasion, lymph node metastasis, and histological grade. In the study by Kim et al, it was observed that lesions with negative PR and high Ki-67 proliferation index had high stiffness rates, as obtained with SWE 23 . Similarly, Gu et al showed significant correlations between lymph node metastasis, histological grade, and SWE stiffness rates.…”
Section: Discussionmentioning
confidence: 79%
“…20 21 This aging process applies to the penile CC and results in a decline in erectile function. 8 9 10 SWE is a noninvasive method to measure differences in tissue structure, and it is widely used in the differential diagnosis of breast, 22 prostate, 23 and liver 24 diseases. In the current study, we used SWE to evaluate the tissue structure of the CC.…”
Section: Discussionmentioning
confidence: 99%